2010
DOI: 10.1097/bot.0b013e3181dc50cd
|View full text |Cite
|
Sign up to set email alerts
|

Radiographic Quantification and Analysis of Dysmorphic Upper Sacral Osseous Anatomy and Associated Iliosacral Screw Insertions

Abstract: Dysmorphic S1 segments are anatomically competent for routine screw fixation. The S2 segment provides a larger osseous site for screw insertion than S1 in dysmorphic sacrums. Significantly longer screws are possible in S2 compared with the dysmorphic S1 segment. S2 iliosacral screws can be safely and accurately accomplished using a standard technique in patients with unstable posterior pelvic ring disruptions and sacral dysmorphism. Safe screw insertions avoid iatrogenic nerve root injuries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
89
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 106 publications
(96 citation statements)
references
References 18 publications
3
89
2
Order By: Relevance
“…With wider use of screw fixations in different positions in the posterior pelvic ring (iliosacral or transsacral), several morphologic variations were described and the terms ''dysplastic sacrum'' and ''sacral dysmorphism'' were introduced, however, there is lack of consensus regarding their definitions [2,4,7,22,29]. Routt et al [29] described five qualitative radiographic signs for sacral dysplasia based on pelvic-outlet and true lateral views, whereas quantitative parameters were described by others [17,22].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…With wider use of screw fixations in different positions in the posterior pelvic ring (iliosacral or transsacral), several morphologic variations were described and the terms ''dysplastic sacrum'' and ''sacral dysmorphism'' were introduced, however, there is lack of consensus regarding their definitions [2,4,7,22,29]. Routt et al [29] described five qualitative radiographic signs for sacral dysplasia based on pelvic-outlet and true lateral views, whereas quantitative parameters were described by others [17,22].…”
Section: Discussionmentioning
confidence: 99%
“…A triangle ratio of 1.5 (calculated by the quotient of the anterior height and width of the first sacral body) represents the boundary ratio for the prevalence of sacral dysmorphism, defined as transsacral corridors with a diameter less than 7.3 mm, unsuitable for screw placement. In contrast to these studies, we defined sacral dysmorphism as the absence of a transsacral corridor at the level of the S1 vertebra, as a high sacral anatomic variability [4] and different corridor diameter cutoffs (5, 9, or 10 mm) exist for transsacral implant placement based on the implant types used (screws, bars, or nails), implant sizes (5-8 mm diameters), and insertion technique (fluoroscopic-controlled versus computer-guided navigation) [2,5,8,11,21,24,37]. Our study provides additional information regarding transsacral corridor-size distributions and proportions of pelves based on their individually set cutoffs in clinical settings (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The morphology of the osseous corridor in upper sacral segment dysplasia has been previously described as having five associated qualitative characteristics identifiable on an outlet radiograph [28][29][30] . Patients with the qualitative characteristics of upper sacral segment dysplasia have narrower and more angulated upper sacral segments 29 .…”
mentioning
confidence: 99%
“…Gardner et al (12) reported that the orientations and cross-sections of the safe bone pathway are quite different between the normal and dysmorphic sacra, and they recommended S2 to be a primary zone for the fixation of the dysmorphic sacra. Similarly, in another CT imaging study, Conflitti et al (8) reported that the second upper sacral segment had a larger and longer safe bone pathway when compared to the first one, which was also anatomically competent for screw fixation.…”
Section: Introductionmentioning
confidence: 81%
“…The dysmorphic upper sacral anatomy provides consistent yet atypical alar pedicle (so-called safe zone or osseous pathway) sizes and angles that mandate very important technical and radiographic alterations when S1 and S2 sacral segment iliosacral screws are to be placed (3)(4)(5)(6)(7)(8). Considering the potential risks of percutaneous iliosacral fixation, which include neurovascular damage (8)(9)(10)(11), some of the researchers working in the field have attempted to quantify the upper sacral morphology of normal and dysmorphic sacra by CT-based studies (8,12,13). Gardner et al (12) reported that the orientations and cross-sections of the safe bone pathway are quite different between the normal and dysmorphic sacra, and they recommended S2 to be a primary zone for the fixation of the dysmorphic sacra.…”
Section: Introductionmentioning
confidence: 99%